Síntese de pigmentos cerâmicos inorgânicos nanométricos pela rota dos precursores poliméricos - Silva, Everlânia Maria da (2011)
Considering the constant evolution of technology in growth and the need for production techniques in the ceramics area to move forward together, we sought in this study, the research and development of polymeric precursor method to obtain inorganic ceramic pigments. Method that provides quality to obtain the precursor powders of oxides and pigments at the same time, offers time and cost advantages, such as reproducibility, purity and low temperature heat treatment, control of stoichiometry. This work used chromium nitrate and iron nitrate as precursors. The synthesis is based on the dissolution of citric acid as a complexing agent, addition of metal oxides, such as ion chromophores; polymerization with ethylene glycol and doping with titanium oxide. Passing through precalcination, breakdown, thermal treatments at different temperatures of calcination (700 to 1100 oC), resulting in pigments: green for chromium oxide deposited on TiO2 (CrTiO3) and orange for iron oxide deposited on TiO2 ( FeTiO3). Noticing an increase of opacity with increasing temperature. Were performed thermal analysis (TG and ATD) in order to evaluate its thermodecomposition. The powders were also characterized by techniques such as XRD, revealing the formation of crystalline phases such as iron titanate (FeTiO3) and chrome titanate (CrTiO3), SEM, demonstrating formation of rounded particles for both oxides and Spectroscopy in the UV-Visible Region, verifying the potential variation and chromaticity os pigments. Thus, the synthesized oxides were within the requirements to be applied as pigments and shown to be possible to propose its use in ceramic materials